2005
DOI: 10.1128/aem.71.12.8371-8382.2005
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequences of Four Plasmids ofLactococcus lactissubsp.cremorisSK11 Reveal Extensive Adaptation to the Dairy Environment

Abstract: Lactococcus lactis strains are known to carry plasmids encoding industrially important traits. L. lactis subsp. cremoris SK11 is widely used by the dairy industry in cheese making. Its complete plasmid complement was sequenced and found to contain the plasmids pSK11A (10,372 bp), pSK11B (13,332 bp), pSK11L (47,165 bp), and pSK11P (75,814 bp). Six highly homologous repB-containing replicons were found, all belonging to the family of lactococcal theta-type replicons. Twenty-three complete insertion sequence elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
169
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(179 citation statements)
references
References 78 publications
6
169
0
2
Order By: Relevance
“…The isolates of the other genetic lineages harbored a single unique plasmid profile for their corresponding lineage (Figure 4). Analogous to the previous reports (Feirtag et al, 1991;Siezen et al, 2005), functions that are relevant for growth in a dairy environment were found to be plasmid associated, including the citrate transport encoding gene (citP), extracellular protease (prtP) and lactose utilization (lac-operon; lacG) ( Supplementary Figure 8). On the basis of this analysis, cross-lineage plasmid transfer appears to be operational but not all host-plasmid combinations were encountered, suggesting certain incompatibilities.…”
Section: Metabolic Complementation Of Lactococcus and Leuconostocmentioning
confidence: 50%
“…The isolates of the other genetic lineages harbored a single unique plasmid profile for their corresponding lineage (Figure 4). Analogous to the previous reports (Feirtag et al, 1991;Siezen et al, 2005), functions that are relevant for growth in a dairy environment were found to be plasmid associated, including the citrate transport encoding gene (citP), extracellular protease (prtP) and lactose utilization (lac-operon; lacG) ( Supplementary Figure 8). On the basis of this analysis, cross-lineage plasmid transfer appears to be operational but not all host-plasmid combinations were encountered, suggesting certain incompatibilities.…”
Section: Metabolic Complementation Of Lactococcus and Leuconostocmentioning
confidence: 50%
“…S1), and putative D-Ldhs are only found in L. lactis plasmids pSK11P and pGdh442. Siezen et al (2005) (Tanous et al, 2007). Hence, there is no proof that the D-Ldh homologues found on pGdh442 and pSK11L are functional (Tanous et al, 2007;Siezen et al, 2005).…”
Section: Metabolic Functions Encoded By Plp712mentioning
confidence: 97%
“…Siezen et al (2005) (Tanous et al, 2007). Hence, there is no proof that the D-Ldh homologues found on pGdh442 and pSK11L are functional (Tanous et al, 2007;Siezen et al, 2005). The pLP712_45 gene product has homology (Table S2) with an aketoacid dehydrogenase (E3 lipoamide dehydrogenase; Lpd), which is part of a family of multicomplex enzymes with many roles in metabolism that includes pyruvate dehydrogenase, a-ketoglutarate dehydrogenase, acetoin dehydrogenase, branched-chain a-ketoacid dehydrogenases (and the glycine cleavage system), depending on the bacterial species (Hein & Steinbüchel, 1994;Smith et al, 2002;Krüger et al, 1994).…”
Section: Metabolic Functions Encoded By Plp712mentioning
confidence: 99%
See 1 more Smart Citation
“…This incompatibility could explain why the majority of strains exhibiting GDH activity carried by pGdh442 have been isolated from a plant or animal environment, while this activity has only rarely been detected in L. lactis strains with a history in dairy fermentation (Tanous et al, 2002). However, pGdh442 is probably compatible with the two plasmids that separately carry the genes responsible for lactose-fermenting ability and casein utilization in L. lactis SK11, because of the very low homology of their iterons (Siezen et al, 2005). …”
mentioning
confidence: 96%